Traumatic dental injures on maxillary incisors and its sequelae after 22-years follow-up: a case report (Research, Society and Development, 2020)
Avulsion of a permanent tooth is a serious condition and a true dental emergency that can be associated with other traumatic injuries. In addition, in reimplanted avulsed teeth, ankylosis and external replacement resorption (ERR) are two typical biological responses, with long-term progression and outcome associated with the patient's growth stage. The purpose of this report is to present the long-term outcome of an 18-year-old patient who was the victim of a motor vehicle traffic accident that resulted in traumatic injury to the maxillary incisors, including an avulsed central incisor with extensive external replacement resorption (tooth 11). Twenty-two years later, due to the continuous effect of the ERR process on the reimplanted tooth and favorable bone weight, it was decided to perform rehabilitation with immediate guided implant by a simplified method (KEA-TECH system). In young patients, the decision to maintain the tooth even under unfavorable conditions may delay rehabilitation with implants.